PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, SENSITIVITAS INDUSTRI DAN ANALYST COVERAGE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - Riski, Ahmadi Madi; Anisma, Yuneita; Putra, Adhitya Agri (Economic and Science Faculty of Islamic State University, 2024)
This study aims to analyze and provide empirical evidence regarding the effect of firm size, profitability, industry sensitivity, and analyst coverage on sustainability report disclosure. Sustainability reports are measured using the Sustainability Report Index Disclosure. This study uses secondary data and the population in this study are plantation, mining, and manufacturing companies listed on the Indonesian stock exchange, totaling 243 companies. The sample was selected using the purposive sampling method. Based on the purposive sampling method, the sample obtained in the study was 18 companies. The analytical method used in this study is multiple linear regression analysis with the analysis of (SPSS) version 25.0. The results of this study indicate that the size of the company does not affect the disclosure of the sustainability report. Meanwhile, profitability, industry sensitivity, and analyst coverage affect the disclosure of the sustainability report.